The Meaning of Repentance According to Imam Ghazali and Semantic Analysis in the Qur'an: A Comprehensive Study - Nuraini, Nabilah (West Science Islamic Studies, 2024)
This study investigates the meaning of repentance as articulated by Imam Ghazali and its semantic representation in the Qur'an. By analyzing Imam Ghazali's interpretation of "taubat," the research delves into the spiritual, ethical, and psych thological dimensions of repentance in Islamic teachings. The study uses analysis descriptive as the method and it’s further conducts a semantic analysis of relevant Qur'anic verses to elucidate the concept's theological implications, including divine mercy, forgiveness, and justice. This comprehensive examination aims to bridge classical Islamic scholarship with contemporary semantic analysis, offering a nuanced understanding of repentance's role and significance in Islam. The findings contribute to Islamic studies, religious studies, and theological scholarship, providing valuable insights into the multifaceted nature of repentance or "taubat" and its contemporary relevance.